PHASE COMPOSITION OF ALLOYED BRASSES IN CAST AND HEAT-TREATED STATE - V. S. Shumihin; V. V. Plitchenko; V. L. Lahnenko (Литьë и металлургия)
Influence of Si, Al, Ni, Fe, Mn alloying on proportion of α and β-phases in brasses with equivalent concentration of zinc 33—38% in cast state and after annealing is shown.